Bamboo-inspired self-powered triboelectric sensor for touch sensing and sitting posture monitoring. (January 2022) - Lei, Hao; Xiao, Jie; Chen, Yunfeng; Jiang, Jiwei; Xu, Renjie; Wen, Zhen; Dong, Bin; Sun, Xuhui
Abstract: Self-powered sensors, as the essential information notes in low power consumption of Internet of healthcare, exhibit a great potential to monitor the state of human health in real time. In this work, a bamboo-inspired self-powered triboelectric sensor (BSTS) using 3D-printing and freeze-drying fabrication processes is presented. The designed triboelectric layer with hollow and bamboo-joint microstructures has a low equivalent stiffness coefficient and a great deformation limit, contributing significantly to the high sensitivity and wide detection range of BSTS. An electromechanical model was proposed to better understand the influence mechanism of inner structures in the dielectric layer on the sensing performance. The sensitivity of the BSTS can reach 3.627 kPa −1 in the pressure range of 0–8 kPa and still keep 1.264 kPa −1 in the range of 8–80 kPa. Moreover, the BSTS is able to detect tiny pressure as low as 5 Pa and possesses ultra-fast response time of 40 ms. A touch-controlled lighting system and a sitting posture monitoring system based on the BSTS for healthcare application are demonstrated. This strategy paves a way to fabricate the self-powered triboelectric pressure sensor with high sensitivity in all working ranges. Graphical Abstract: ga1 Highlights: A bamboo-inspired self-powered triboelectric sensor (BSTS) using 3D-printing and freeze-dryingtechlog is fabricated. The hollow and bamboo-joint microstructures with a low stiffness coefficient and a great deformation limit. The sensitivity can reach 3.627 kPa −1 in the pressure range of 0–8 kPa and keep 1.264 kPa −1 in the range of 8–80 kPa. The BSTS can detect tiny pressure as low as 5 Pa in ultra-fast response time(40 ms). A touch-controlled lighting system and a sitting posture monitoring system based on the BSTSare demonstrated.